Development of a spatialdynamical model of the structure of clumps of toxic cyanobacteria for biosafty purposes - Vуsotska, Olena; Georgiyants, Marine; Nosov, Kostiantyn; Balym, Yurii; Pecherska, Anna; Porvan, Andrii; Pavlov, Sergey; Shekhovtsova, Victoriya; Klochko, Tetiana; Solodovnikov, Andrii (Eastern-European Journal of Enterprise Technologies, 2018)
We have devised a spatialdynamic model that describes the structure of clusters of toxic cyanobacteria over large water areas. The application of the constructed model has been demonstrated in order to identify the structure of a cluster in digital photographs. The character of bioproductive processes that define the risk of accumulation of toxic microorganisms is determined by a series of parameters that can be measured remotely using aerospace methods (taking photographs). The proposed model, based on a digital image, makes it possible to restore the spatialdynamic pattern of clusters by determining the state of bioproductive processes in different parts of the cluster. Information about such states is of great importance in order to optimize measures for eliminating the threat of toxicity. Development of a given spatiallydynamic model is related to the need to identify the structure of clusters of toxic cyanobacteria in water areas in order to eliminate the threats to biosecurity. Such clusters are extremely complex objects and are not reproduced by either theoretical or fullscale models. The constructed spatialdynamic model makes it possible to discover a dynamic pattern of bioproductive processes in different parts of the accumulation of microorganisms. The applied significance of the results obtained is associated with increasing the effectiveness of measures for elimination of the threat of toxicity; in other words, given the model that we constructed, it becomes possible to detect the most effective plots in terms of eliminating the threat. The result of employing the model to the digital images of toxic cyanobacteria agrees well with the hydrobiological realization of this type of objects